The seed of promise: the sufferings and glory of the messiah : essays in honor of T. Desmond Alexander - Williamson, Paul R.; Cefalu, Rita F. (GlossaHouse, 2020)
The skull crushing seed of the woman: Inner-biblical interpretation of Genesis 3:15 / James M. Hamilton -- Weal and woe in Genesis / David A. Baker -- Ephraim or Judah: Divine sovereignty and the potential for kingship in Joshua-Judges / Sarah Dalrymple -- Messianic trajectories in Ruth: A redeemer and a great name / James McKeown -- We three kings: An examination of the messianic trajectory of the books of kings with special reference to Solomon, Hezekiah and Josiah / J. Gary Millar -- The end of history and the last man / Stephen G. Dempster -- Suffering saints, glorious kings, and divine deliverance: Context and relecture in the Psalms / Philip S. Johnston -- Wisdom's testimony to messiah's sufferings and glory / Graeme Goldsworthy -- Rhetoric and truth in Isaiah: An approach to messianic interpretation in the Old Testament -- J. Gordon McConville -- Kings and kingdom in the book of Isaiah / John N. Oswalt -- The messiah in the book of the twelve: Glory through suffering / Anthony R. Petterson -- The sufferings and glory of messiah in the gospel of Mark: Reflections on the transfiguration (Mark 9:1-13) -- The cosmic drama and the seed of the serpent: An exploration of the connection between Genesis 3:15 and Johannine theology / Andreas J. Kostenberger -- The sufferings and glory of Jesus the messiah in Acts 2-3 / Rita F. Cefalu -- Romans 16:20a as a summary of central themes of Romans / Brian S. Rosner -- Hebrews, Melchizedek, and biblical theology / Stephen Motyer -- Snakes and dragons: A neglected theological trajectory of Genesis 3:15 in scripture? / Paul R. Williamson.